Long-Run Determinants of Economic Growth in South America. Issue 1 (1st May 2016) - Vedia-Jerez, Daniel H.; Chasco, Coro
Abstract : Based on an annual historical database for South American countries from 1960 to 2008, we develop an empirical study to gain insight into the long-run determinants of economic growth using a two-equation framework. A system of two panel data models is estimated to identify the growth determinants and their connection with foreign direct investment. We find that economic growth is driven most strongly by physical and human capital accumulation, as well as by sectorial exports, and that institutions and policy have a substantial impact on economic growth and investment. Macroeconomic disturbances have a significant detrimental effect on long-run growth. Trade openness correlates positively with foreign investment, indicating that relatively closed countries stand to benefit most from opening up their economies. Our division of the sample into two sub-periods, 1960–1980 and 1981–2008, indicates a structural change.